The Influence of Deposit Interest Rates, BI 7 Day Reverse Repo Rate and Inflation on the Composite Stock Price Index in BEI during the 2020 - 2022 Pandemic - Anastasya Tindaon; Tri O. Rotinsulu; Mauna Th. B. Maramis (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine and understand the potential relationship between inflation, BI 7-day reverse repo rate, and deposit interest rates on the JCI movement in 2020 to 2022. The research approach used is a quantitative descriptive variation. This method uses three years of observational secondary data, to be precise from 2020 to 2022. Using Eviews 12 software, statistical tests and multiple regression analysis techniques are used in the data analysis process. The findings of this study show that the BI 7-day reverse repo rate and deposit interest rates both have quite a large and beneficial influence on the JCI movement. These results provide important information regarding stock market dynamics and economic variables that influence fluctuations in the IHSG value during the specified research period.